Whistlin' and Crowin' Women of Appalachia : Literacy Practices Since College - Sohn, Katherine Kelleher (Book collections on Project MUSE., 2006)
Even some enlightened academicians automatically-and incorrectly-connect illiteracy to Appalachia, contends Katherine Kelleher Sohn. After overhearing two education professionals refer to the southern accent of a waiter and then launch into a few redneck jokes, Sohn wondered why rural, working-class white people are not considered part of the multicultural community. Whistlin' and Crowin' Women of Appalachia: Literacy Practices since College examines the power of women to rise above cultural constraints, complete their college degrees, assume positions of responsibility, and ultimately come t.